Efficacy of Mesoglycan in Pain Control after Excisional Hemorrhoidectomy: A Pilot Comparative Prospective Multicenter Study. (19th March 2018) - Gallo, Gaetano; Mistrangelo, Massimiliano; Passera, Roberto; Testa, Valentina; Pozzo, Mauro; Perinotti, Roberto; Lanati, Ivan; Lazzari, Ivano; Tonello, Paolo; Ugliono, Elettra; De Luca, Emilia; Realis Luc, Alberto; et al.
Abstract : Introduction . Various pain management strategies for patients undergoing open excisional hemorrhoidectomy have been proposed, yet postoperative pain remains a frequent complaint. Objective . To determine whether mesoglycan (30 mg two vials i.m. once/day for the first 5 days postoperative, followed by 50 mg 1 oral tablet twice/day for 30 days) would reduce the edema of the mucocutaneous bridges and thus improve postoperative pain symptoms. Patients and Methods . For this prospective observational multicenter study, 101 patients undergoing excisional diathermy hemorrhoidectomy for III-IV degree hemorrhoidal disease were enrolled at 5 colorectal referral centers. Patients were assigned to receive either mesoglycan (study group SG) or a recommended oral dose of ketorolac tromethamine of 10 mg every 4–6 hours, not exceeding 40 mg per day and not exceeding 5 postoperative days according to the indications for short-term management of moderate/severe acute postoperative pain, plus stool softeners (control group CG). Results . Postoperative thrombosis (SG 1/48 versus CG 5/45) (p < 0.001 ) and pain after rectal examination (p < 0.001 ) were significantly reduced at 7–10 days after surgery in the mesoglycan-treated group, permitting a faster return to work (p < 0.001 ); however, in the same group, the incidence of postoperative bleeding, considered relevant when needing a readmission or an unexpected outpatient visit, was higher, possibly owing to the drug's antithrombotic properties. Conclusions . The administration of mesoglycan after an open diathermy excisional hemorrhoidectomy can reduce postoperative thrombosis and pain at 7–10 days after surgery, permitting a faster return to normal activities.